CELESTIA: Cost-Effectiveness Analysis of Empagliflozin Versus Sitagliptin in Patients with Type 2 Diabetes in Greece - Ghetti G; Pradelli L; Papageorgiou G; Karpouzos G; Arikan Y (Dove Medical Press, 2023)
Gianni Ghetti,1 Lorenzo Pradelli,1 Giannis Papageorgiou,2 George Karpouzos,2 Yelda Arikan3 1AdRes Health Economics and Outcome Research, Turin, Italy; 2Boehringer Ingelheim Hellas, Athens, Greece; 3Boehringer Ingelheim, Amsterdam, the NetherlandsCorrespondence: Gianni Ghetti, AdRes Health Economics and Outcome Research, Via Vittorio Alfieri, 17, Turin, 10121, Italy, Email g.ghetti@adreshe.comPurpose: Globally, the prevalence of diabetes is on the rise, with the number of affected individuals predicted to cross 700 million by 2045. In Greece, in 2015, almost 700,000 people received prescribed medication for type 2 diabetes. The CELESTIA study aims to assess the cost-effectiveness of empagliflozin compared to branded sitagliptin in type 2 diabetes patients both with and without established cardiovascular disease in Greece from a third payer perspective.Methods: The IQVIA Core Diabetes Model was used and analyses were conducted from the Greek healthcare payer perspective. Patients received either empagliflozin or sitagliptin until HbA1c threshold of 8.5% (69 mmol/mol) was exceeded. Subsequently, patients were assumed to intensify to insulin therapy. Baseline cohort characteristics and treatment effects were derived from clinical trial data. Literature data were used for input (utilities, treatment costs and costs of diabetes-related complications costs). A lifetime time horizon (50 years) was applied, and costs and benefits were discounted at an annual rate of 3.5%.Results: Over a lifetime horizon, for empagliflozin, the estimated ICER was of € 6,587 and € 966 per quality-adjusted life years gained versus sitagliptin, in patients without established cardiovascular disease and in patients with established cardiovascular disease, respectively. Probabilistic sensitivity analysis confirmed the robustness of the analysis.Conclusion: The analysis demonstrated that for type 2 diabetes patients, empagliflozin is a cost-effective treatment option versus branded sitagliptin in Greece.Keywords: cost-effectiveness, empagliflozin, Greece, IQVIA core diabetes model, sitagliptin, type 2 diabetes